The LENT index predicts 30 day outcomes following hospitalization for heart failure. (2nd December 2020) - Van Spall, Harriette GC; Averbuch, Tauben; Lee, Shun Fu; Oz, Urun Erbas; Mamas, Mamas A; Januzzi, James Louis; Ko, Dennis T
Abstract: Aims: The LE index (L ength of hospitalization plus number of E mergent visits ≤6 months) predicts 30 day all‐cause readmission or death following hospitalization for heart failure (HF). We combined N‐terminal pro‐B type natriuretic peptide (NT‐proBNP) levels with the LE index to derive and validate the LENT index for risk prediction at the point of care on the day of hospital discharge. Methods and results: In this prospective cohort sub‐study of the Patient‐centred Care Transitions in HF clinical trial, we used log‐binomial regression models with LE index and either admission or discharge NT‐proBNP as the predictors and 30 day composite all‐cause readmission or death as the primary outcome. No other variables were added to the model. We used regression coefficients to derive the LENT index and bootstrapping analysis for internal validation. There were 772 patients (mean [SD] age 77.0 [12.4] years, 49.9% female). Each increment in the LE index was associated with a 25% increased risk of the primary outcome (RR 1.25, 95% CI 1.16–1.35; C‐statistic 0.63). Adjusted for the LE index, every 10‐fold increase in admission and discharge NT‐proBNP was associated with a 48% (RR 1.48; 95% CI 1.10, 1.99; C‐statistic 0.64; net reclassification index [NRI] 0.19) and 56% (RR 1.56; 95% CI 1.08, 2.25; C‐statistic 0.64; NRI 0.21) increased risk of the primary outcome, respectively. The predicted probability of the primary outcome increased to a similar extent with incremental LENT, regardless of whether admission or discharge NT‐proBNP level was used. Conclusions: The point‐of‐care LENT index predicts 30 day composite all‐cause readmission or death among patients hospitalized with HF, with improved risk reclassification compared with the LE index. The performance of this simple, 3‐variable index ‐ without adjustment for comorbidities ‐ is comparable to complex risk prediction models in HF.